Application of FK Filtering for Coherent Noise Removal in High Frequency Shallow Marine Data - Herman, M. (Institute of Physics Publishing, 2017)
The use of seismic reflection to study earth subsurface is commonly troubled by the presence of the coherent noise in the seismic data. This unwanted signal were generated by various sources and therefore had their own noise characteristic. The acquisition of the shallow marine seismic survey were done using a sparker source to obtain a high frequency seismic data. This however results in a stronger noise level in the recorded data. The application of FK filter were used to eliminate this unwanted noise using the data obtained from the Malacca Strait and Terengganu Bay. The result obtained prove to be successful in reducing the coherent noise while preserving the frequency content of the seismic data. © Published under licence by IOP Publishing Ltd.